Antioxidant, antimicrobial, mineral, volatile, physicochemical and microbiological characteristics of traditional home-made Turkish vinegars - Ozturk, Ismet; Caliskan, Oznur; Tornuk, Fatih; Ozcan, Nihat; Yalcin, Hasan; Baslar, Mehmet; Sagdic, Osman (ELSEVIER SCIENCE BV, 2015)
In the current study, twenty traditional home-made vinegars collected from different regions of Turkey were characterized in terms of their antioxidant, antimicrobial, mineral and volatile profiles as well as their physicochemical and antimicrobial properties and microbiota. The vinegars were compared to five industrial vinegars according to the characterized properties. Industrial vinegars showed quite high antimicrobial activity while only three traditional vinegars had antimicrobial activity for the all test microorganisms. With respect to these results, traditional vinegars had generally high microbial load; however, they were scarcely detected in industrial vinegars. Physicochemical properties of all vinegars were extremely variable. A total of 61 volatile compounds were determined in the traditional vinegars. The most abundant compounds were a-terpineol and ethyl acetate in some traditional vinegars, while phenethyl alcohol was a common compound detected in the vinegars. Mineral profile of traditional vinegar was determined by using ICP-MS. The most abundant minerals were Na, K and Ca in the vinegars. As a conclusion, traditional Turkish vinegars exhibited very distinct properties independent from raw materials used. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Vinegar; Home-made; Antioxidant; Mineral; Volatile; ACETIC-ACID BACTERIA; BALSAMIC VINEGAR; WINE VINEGAR; FERMENTATION; FEASIBILITY; QUALITY; COLOR; Food Science & Technology